AN ANALYSIS OF THE SECOND YEAR STUDENTS’ ABILITY IN CONSTRUCTING COMPOUND SENTENCES AT ENGLISH DEPARTMENT OF UNIVERSITAS NEGERI PADANG - Fairisha Embriany; Hermawati Syarif; Fitrawati Fitrawati (Universitas Negeri Padang, 2018)
This descriptive research aimed to find out the second year students’ ability and the mistakes often done by the students in constructing compound sentences at English Department of Universitas Negeri Padang. The sample of this research was 22 NK1-2017 students of 214 second year students at English Department. The sample was taken by using cluster random sampling. The instrument used was a grammar test consisting of 30 items about compound sentences. The students’ answers were used as the source of the data analyzed. The data was analyzed based on the theory adapted from LeBlanc (2008) and graded based on Peraturan Akademik Universitas Negeri Padang (2015). Based on the findings, it was found that the second year students’ ability in constructing compound sentences was fairly good. Moreover, it was found that the most frequent mistake often done by the students was about the tense and conjugation of verbs which occurred 222 times (25.5%) from 872 mistakes found. Based on those findings, it can be concluded that the students quite understand how to construct compound sentences. Moreover, the mistakes related to the tense and conjugation of verbs occurred because the sentence written by the students had clauses containing verbs that were not in the correct tense, inappropriately singular/ plural, and otherwise do not agree with the subject.